Game Based Learning Design and Development for Effective Instructional Process at Senior High School Level - Setiawan, Budi (Universitas Pendidikan Ganesha, 2023)
Information and Communication Technology (ICT) helps people learn is becoming more and more common in the teaching process. This lets learners keep learning by using their mobile devices to access their learning tools. On the other hand, language teachers, who are often both users and creators of teaching and learning activities, do not always know how to use and apply the steps on designing the lesson by infiltrating technology. The purpose of this study is to develop the efficacy of game-based learning multimedia in enhancing student-learning outcomes in the classroom with regard to English grammar. The research development of multimedia game-based learning using the Raiser and Demsey procedure. The trial of product development had passed multiple processes, including: the review from a media expert, which included software changes and visual communication; the review from a content expert, which included material and instructional design; the responses of students to the product's usability and attractiveness; and the review from a content expert. The implication of this study is that the language learning design with the ICT approach is able to fulfil the needs and skills of students. Gamification can enhance the learning process because it can engage and motivate students with games.